فعالية المراجعة الخارجية للقوائم المالية في كشف ممارسات المحاسبة الإبداعية - المولدي, محبوب; فرجاني, محمد الصالح; عوني, محمد الصغير (University of eloued جامعة الوادي, 2018)
The concept of creative accounting has become a focus of attention by auditors. Through this topic, entitled "The Effectiveness of External Review of Financial Statements in Disclosure of Creative Accounting Practices," we have highlighted the role of the auditor in disclosing and reducing creative accounting manipulations on the financial statements. In order to achieve the objectives of the study, the descriptive analytical method was used by collecting the data obtained through the distribution of the questionnaire lists on a sample of the study population of 75 individuals and after the data was collected, collected and analyzed using SPSS 21 and EXCEL 2007
مذكرة ماستر محاسبة
Keywords: المراجعة الخارجية، المحاسبة الابداعية; Creative Accounting , External Audit